2010
DOI: 10.3945/ajcn.2009.29099
|View full text |Cite
|
Sign up to set email alerts
|

Intake of carbohydrates compared with intake of saturated fatty acids and risk of myocardial infarction: importance of the glycemic index

Abstract: Background: Studies have suggested that replacing saturated fatty acids (SFAs) with carbohydrates is modestly associated with a higher risk of ischemic heart disease, whereas replacing SFAs with polyunsaturated fatty acids is associated with a lower risk of ischemic heart disease. The effect of carbohydrates, however, may depend on the type consumed. Objectives: By using substitution models, we aimed to investigate the risk of myocardial infarction (MI) associated with a higher energy intake from carbohydrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 19 publications
3
126
1
9
Order By: Relevance
“…To our knowledge, no previous studies have separately reported the associations of low-, medium-or high-GI carbohydrate intake and type 2 diabetes risk, while recently analyses on risk of coronary heart disease have been published. 21,22 The main contributor foods of low-GI carbohydrates were milk and fruits, vegetables and legumes, of medium-GI carbohydrates added sugar and sugary foods and of high-GI carbohydrates wheat bread and bakeries, rye bread and potatoes. 20 The inverse association between medium-GI carbohydrate intake and diabetes risk is in keeping with the findings from some previous cohort studies, suggesting inverse association between sugar intake and diabetes risk.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous studies have separately reported the associations of low-, medium-or high-GI carbohydrate intake and type 2 diabetes risk, while recently analyses on risk of coronary heart disease have been published. 21,22 The main contributor foods of low-GI carbohydrates were milk and fruits, vegetables and legumes, of medium-GI carbohydrates added sugar and sugary foods and of high-GI carbohydrates wheat bread and bakeries, rye bread and potatoes. 20 The inverse association between medium-GI carbohydrate intake and diabetes risk is in keeping with the findings from some previous cohort studies, suggesting inverse association between sugar intake and diabetes risk.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the EPIC-Netherlands cohort replacing 5% of energy from SFA with carbohydrate was associated with an increased risk of IHD [31]. In contrast, replacing 5% of calories from SFA with carbohydrate was not associated with a reduction in risk of MI in a Danish cohort [101].…”
Section: Replacing Sfa With Carbohydratesmentioning
confidence: 99%
“…Replacing SFA with low GI carbohydrates (GI<53) was not associated with a change in IHD risk [31]. Similarly, Jakobsen et al found no significant change in MI risk when 5% of energy from SFA was replaced by low GI (median GI 82) or medium GI (median GI 88) carbohydrates [101].…”
Section: Replacing Sfa With Carbohydratesmentioning
confidence: 99%
“…Derved blir «grove» og «raffinerte» kilder til karbohydrater satt sammen til en kategori, noe som er problematisk. Derimot ser utskifting av mettet fett med lavglykemiske karbohydratkilder med mye fiber ut til å vaere gunstig 206,207 . Tabell I tillegg til metaanalysene i tabell 25 fant både Ramsden og Hooper og medarbeidere at et høyere inntak av flerumettet fett på bekostning av mettet fett reduserte risikoen for hjerte-og kar-hendelser (se kapittel 7C) 126,148,149 .…”
Section: Nasjonale Og Faglige Anbefalingerunclassified
“…En reduksjon av mettet fett til fordel for kostfiber kan også vaere gunstig, blant annet for energitettheten 206,207 .…”
unclassified